Students’ Perspectives on TOEFL Training Program in an Islamic Boarding School - Hadi, Iwan (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This study aims to explore students’ perspectives to the TOEFL training program conducted at an Islamic boarding school in Mojokerto, using a descriptive qualitative approach. The study involves six student participants and two teachers to provide a comprehensive understanding of the program’s reception and effectiveness. Data were collected through interviews, observations, and document analysis, guided by Kirkpatrick’s reaction theory, which emphasizes participants’ perceptions of a training program in terms of satisfaction, engagement, and relevance to their needs. Findings reveal that students generally perceive the program as beneficial for enhancing their English proficiency, particularly in listening and reading skills, which are crucial components of the TOEFL test. Positive reactions include appreciation for the program’s interactive teaching methods, clear instructions, and supportive learning environment. However, challenges such as limited time allocation, inadequate materials, and difficulty in grasping complex grammar topics were also identified. Teachers noted an improvement in students’ confidence and motivation, but they also highlighted the need for more comprehensive resources and additional training sessions to ensure better outcomes.